Quality and Delivery Costs of Wood Chips by Railway vs. Road Transport - Mariusz Jerzy Stolarski (MDPI AG, 2021)
Forests are the main sources of wood chips delivered to the end customers by road or railway. This research analysed the impact of the quarter of the year: Q1 (January–March), Q2 (April–June), Q3 (July–September), Q4 (October–December) when wood chips were obtained over two consecutive years (2019–2020) and the type of transport used (railway and road) on the thermophysical properties of wood chips and the cost of their delivery. The mean moisture content in the wood chips was 38.28% and it was the highest (45.55%) in Q1, while in Q2 and Q3, this parameter was 8 and 17 percentage points (p.p.) lower. The mean lower heating value (LHV) of the chips was 10.46 GJ Mg−1. The chips delivered by road transport had a 4% higher LHV compared to those shipped by railway transport. The wood chips contained 3.42% d.m. of ash. The road transport at a distance of 200 km was found to be approximately 10% cheaper compared to the transport by rail for most of the study period, both with respect to 1 Mg of fresh or dry mass and 1 GJ of energy in the chips. The railway transport was cheaper in the winter (Q1).